Channel quantization techniques for hybrid massive MIMO millimeter wave systems - Lopes, André Daniel Carvalho (2017)
Since the appearance of mobile communications, the users of this technology have been growing exponentially every day. The escalating mobile traffic growth it has been imposed by the proliferation of smartphones and tablets. The increasing and more intensive use of wireless communications may lead to a future breaking point, where the traditional systems will fail to support the required capability, spectral and energy efficiency. On the other hand, to cover all this current need to have more and more data it is necessary to provide a new range of data rates around the gigabits per second. Today, almost all mobile communications systems use spectrum in the range of 300MHz – 3GHz. It is needed to start looking to the range of 3GHz – 300GHz spectrum for mobile broadband applications. Millimeter waves are one way to alleviate the spectrum gridlock at lower frequencies. MIMO based systems has been researched for the last 20 years and are now part of the current standards. However, to achieve more gains, a grander view of the MIMO concept envisions the use of a large scale of antennas at each base stations, a concept referred as massive MIMO. The symbiotic combination of these technologies and other ones will lead to the development of a new generation system known as the 5G. The knowledge of the channel state information at the transmitter is very important in real massive MIMO millimeter wave systems. In this dissertation a limited feedback strategy for a hybrid massive MIMO OFDM system is proposed, where only a part of the parameters associated to the link channel are quantized and fed back. The limited feedback strategy employs a uniform-based quantization for channel amplitudes, angle of departure and angle of arrival in time domain. After being fed back, this information is used to reconstruct the overall channel in frequency domain and the transmit antenna array, which are then used to compute the hybrid analog-digital precoders. Numerical results show that the proposed quantization strategy achieve a performance close to the one obtained with perfect full channel, with a low overhead and complexity